Inhibition of the CSF‐1 receptor sensitizes ovarian cancer cells to cisplatin. (25th January 2018) - Yu, Rong; Jin, Hao; Jin, Congcong; Huang, Xuefeng; Lin, Jinju; Teng, Yili
Abstract : Ovarian cancer is one of the most common female malignancies, and cisplatin‐based chemotherapy is routinely used in locally advanced ovarian cancer patients. Acquired or de novo cisplatin resistance remains the barrier to patient survival, and the mechanisms of cisplatin resistance are still not well understood. In the current study, we found that colony‐stimulating‐factor‐1 receptor (CSF‐1R) was upregulated in cisplatin‐resistant SK‐OV‐3 and CaoV‐3 cells. Colony‐stimulating‐factor‐1 receptor knockdown suppressed proliferation and enhanced apoptosis in cisplatin‐resistant SK‐OV‐3 and CaoV‐3 cells. However, CSF‐1R overexpression had inverse effects. While parental SK‐OV‐3 and CaoV‐3 cells were more resistant to cisplatin after CSF‐1R overexpression, CSF‐1R knockdown in SK‐OV‐3 and CaoV‐3 cells promoted cisplatin sensitivity. Overexpression and knockdown studies also showed that CSF‐1R significantly promoted active AKT and ERK1/2 signalling pathways in cisplatin‐resistant cells. Furthermore, a combination of cisplatin and CSF‐1R inhibitor effectively inhibited tumour growth in xenografts. Taken together, our results provide the first evidence that CSF‐1R inhibition can sensitize cisplatin‐refractory ovarian cancer cells. This study may help to increase understanding of the molecular mechanisms underlying cisplatin resistance in tumours.